A history of the United States - Jenkins, Philip, 1952- (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2012)
"This established introductory text provides a lucid, authoritative account of the course of American history, discussing political, social, economic and cultural developments. In this revised and updatednew edition, Jenkins discusses the Obama presidency, the economic crisis and recent environmental issues"--
Machine generated contents note: -- List of Tables -- List of Maps -- Preface to the Fourth Edition -- Preface to the Third Edition -- Preface to the Second Edition -- Preface to the First Edition -- Introduction -- Unnamed Lands: The European Settlement, 1492-1765 -- Revolution and Nation Building, 1765-1825 -- Expansion and Crisis, 1825-65 -- Cities and Industry, 1865-1917 -- War and Globalism, 1917-56 -- Only Yesterday: The United States 1956-2000 -- Contemporary America -- Glossary -- Suggestions for Further Reading -- Index.
Includes bibliographical references and index.
Keywords: HISTORY / United States / General; HISTORY / United States / 21st Century; HISTORY / United States / 20th Century; HISTORY / United States / 19th Century; United States -- History